Storytelling as a Strategic Communication Method in Business Presentation - Feri Anugrah (Sahabat Publikasi, 2026)
In an increasingly competitive and digitally connected business environment, companies no longer compete solely through product quality and pricing but also through their ability to communicate messages persuasively and emotionally. Modern business presentations require communication approaches that can build emotional connections with audiences. Storytelling has emerged as a strategic communication method considered effective because it makes messages easier to understand, remember, and emotionally internalize, especially in service industries that heavily rely on trust, such as Umrah and Hajj travel services. This study examines storytelling as a strategic communication method in modern business presentations, using a case study of PT Almira Berkah Abadi. A qualitative approach with a case study design was employed. Data were collected through interviews, field observations, and literature reviews. The findings reveal that storytelling enhances promotional effectiveness, builds emotional closeness, and strengthens public image and trust in the company. Inspirational stories, packaged relevantly and delivered through both live presentations and digital media, have proven effective in expanding message reach and encouraging consumer decisions to use the company’s services. This article provides theoretical and practical contributions for business professionals seeking to optimize storytelling as an impactful communication and marketing tool.